Raw seismic refraction data during cruise RV SONNE SO258/2 (INGON), Indian Ocean off Sri Lanka, profile AWI-20170400 - Weigelt, Estella; Geissler, Wolfram H; Altenbernd-Lang, Tabea; Jokat, Wilfried; Werner, Reinhard
As part of the research project INGON (a collaboration between the Alfred Wegener Institute and the GEOMAR), two offshore seismic refraction profiles were obtained during Sonne cruise SO258 to study the separation of India and Antarctica. The acquired data set covers data of 30 stations recorded with three different types of Ocean Bottom Seismometer (OBS)-systems: 12 LOBSTER and 2 NAMMU systems of the AWI belonging to the DEPAS pool (German Instrument Pool for Amphibian Seismology) and 20 OBS systems of GEOMAR. The raw-data acquired with AWI-OBS were recorded with 6d6-recorders, manufactured by KUM in Kiel, Germany. The AWI-OBS were equipped with a Seismometer (3 channels) and a hydrophone (1 channel). The raw-data of the AWI-OBS is in 6d6-format and can be converted with software from SEND and KUM to segy. The raw-data acquired with GEOMAR-OBS were recorded with Sercel-recorders or Geolog-recorders. The GEOMAR-OBS were equipped with a geophone instead of a seismometer (3 channels) and a hydrophone (1 channel, the hydrophone-channel was recorded 2x). The raw-data of the GEOMAR-OBS was converted to psegy-format (pseudo segy). 21 instruments were deployed for profile AWI-20170400 at an average distance of 13.5 km. The profile extends in a NW-SE direction and crosses the proposed prolongation of the 85°E Ridge. Profiling started on 02 August 2017 at 84.24122°N, 1.12148°E, and ended on 03 August 2017 at 82.37525°N, 3.38.813°E. One OBS (station 407) could not be recovered, one OBS (station 421) did not return data, but all other OBS worked and could be synchronized with the GPS clock upon recovery such that skew values describing the clock drift are available for all stations.The data set provides raw data of OBS-stations concerning the refraction seismic profile AWI-20170300. It comprises (a) seismic station data in 6d6 format or pseudo-segy format depending on the data logger, (b) a list of navigation data with date, time, coordinates in 1 sec intervals (c) a list of shot-numbers and shot times, and (d) a table ...